The Analysis Of Lexical And Structural Ambiguities Found In News Titles Of The Jakarta Post Newspaper And Its Implication To Translation - Raihana*, Esti; Arif, Qonaah Nuryan (Universitas Syiah Kuala, 2023)
This study aims to identify and analyze the ambiguities found in news titles of The Jakarta Post, focusing only on two kind of ambiguities, Lexical Ambiguity and Structural Ambiguity. The objectives of this study are: 1) To analyze the lexical ambiguity news titles found in The Jakarta Post newspaper and the interpretations which may arise. 2) To analyze the structural ambiguity news titles found in The Jakarta Post newspaper and the interpretations which may arise. 3) To describe the cause of ambiguous titles at the Jakarta Post Newspaper. 4) To analyze the implication of ambiguity in translation teaching. The data for this study were taken from The Jakarta Post news titles from February 1 to February 5, 2018. It is a descriptive qualitative study that analyzes the data in the form of words, phrases and sentences descriptively. Based on these research findings, there were 14 ambiguities found. They consisted of seven lexical ambiguities, which are five functioned as nouns and two as verbs. Seven titles were categorized as structurally ambiguous. The causes of lexical ambiguities in news titles are polysemy and homonymy, while the causes of structural ambiguities are equivocal phrasing and contextual ambiguity. This implies that understanding ambiguity, especially lexical and structural ambiguity, can affect the students translation ability.